Current ozone levels threaten gross primary production and yield of Mediterranean annual pastures and nitrogen modulates the response (Atmospheric Environment, 2014)
Pastures are among the most important ecosystems in Europe considering their biodiversity and distribution area. However, their response to increasing tropospheric ozone (O3) and nitrogen (N) deposition, two of the main drivers of global change, is still uncertain. A new Open-Top Chamber (OTC) experiment was performed in central Spain, aiming to study annual pasture response to O3 and N in close to natural growing conditions. A mixture of six species of three representative families was sowed in the field. Plants were exposed for 40 days to four O3 treatments: filtered air, non-filtered air (NFA) reproducing ambient levels and NFA supplemented with 20 and 40 nl l-1 O3. Three N treatments were considered to reach the N integrated doses of “background”, +20 or +40 Kg N ha-1. Ozone significantly reduced green and total aboveground biomass (maximum reduction 25%) and increased the senescent biomass (maximum increase 40%). Accordingly, O3 decreased community Gross Primary Production due to both a global reduction of ecosystem CO2 exchange and an increase of ecosystem respiration. Nitrogen could partially counterbalance O3 effects on aboveground biomass when the levels of O3 were moderate, but at the same time O3 exposure reduced the fertilization effect of higher N availability. Therefore, O3 must be considered as a stress factor for annual pastures in the Mediterranean areas.

Modelling the influence of peri-urban trees in the air quality of Madrid region (Spain). (Environmental pollution (Barking, Essex : 1987), 2011)
Tropospheric ozone (O(3)) is considered one of the most important air pollutants affecting human health. The role of peri-urban vegetation in modifying O(3) concentrations has been analyzed in the Madrid region (Spain) using the V200603par-rc1 version of the CHIMERE air quality model. The 3.7 version of the MM5 meteorological model was used to provide meteorological input data to the CHIMERE. The emissions were derived from the EMEP database for 2003. Land use data and the stomatal conductance model included in CHIMERE were modified according to the latest information available for the study area. Two cases were considered for the period April-September 2003: (1) actual land use and (2) a fictitious scenario where El Pardo peri-urban forest was converted to bare-soil. The results show that El Pardo forest constitutes a sink of O(3) since removing this green area increased O(3) levels over the modified area and over down-wind surrounding areas.